Ostmeyer Family Farms: Economic feasibility of replacing summer fallow with field peas in Northwest Kansas - Ostmeyer, Chase (My University, 2019)
This thesis was completed to study the economic feasibility of replacing summer fallow with field peas in Northwest Kansas and more particularly on Ostmeyer Family Farms. Ostmeyer Family Farms consists of dryland and irrigated farm ground in Thomas and Sheridan County, Kansas. The farm has been in no-till production for the past 20 plus years. To help combat the chemical resistant weeds and improve overall profit per acre, Ostmeyer Family Farms needs to look at alternative management approaches. This thesis outlines one alternative approach to summer fallow. Research was completed regarding the ability to grow field peas and market them in northwest Kansas. This research showed that the climate was particularly suited to grow field peas in northwest Kansas. The field pea market is also available in southern Nebraska, which is feasible to ship by truck. Analysis was completed on each of the following enterprises: i) wheat after fallow, ii) wheat after field peas, iii) chemical fallow, iv) corn, and v) field peas. Each enterprise budget was used to establish a rotational budget of fallow-wheat-corn and field peas-wheat-corn. The fallow-wheat-corn rotational budget resulted in a net loss of ($26.43) per acre, while the field peas-wheat-corn rotational budget resulted in a net loss of ($23.62). For the field pea-wheat-corn rotation to equal the fallow-wheat-corn rotation, field pea price would need to decrease by $0.34 per bushel, yield would need to decrease by 1.24 bushel per acre, or a combination of the two. A worst case scenario was also completed to show what each rotation would be with a totally failed crop. This results in fallow-wheat-corn rotation net loss per acre of ($87.76) and field peas-wheat-corn rotation net income loss per acre of ($115.63). This worst case scenario would favor the fallow-wheat-corn rotation by $27.87/acre. The researcher found that the field pea-wheat-corn rotation would be riskier, but overall more profitable than the fallow-wheat-corn rotation. Based on this research, a field pea-wheat-corn rotation is more economical than a fallow-wheat-corn rotation. The researcher recommends Ostmeyer Family Farms switch from a fallow-wheat-corn rotation to a field peas-wheat-corn with an economic gain currently $2.81 per acre better than the current fallow-wheat-corn rotation. However, it would be beneficial for Ostmeyer Family Farms to experiment with the field pea-wheat-corn rotation on a small acreage, since the difference between each rotation is very minimal. This would allow for them to observe what the actual yield of field peas is on their farm and yield penalty on the follow wheat crop. Doing this on a small acreage would limit the loss if the worst case scenario were to happen. With a slim economical difference between the two rotations, Ostmeyer Family Farms should continue to reassess this with the decision tool provided with this research as prices and inputs change.
Keywords: Field Peas; Enterprise Budget; Fallow; Weed Resistence; Economic Feasibility